Sirt6 in pro-opiomelanocortin neurons controls energy metabolism by modulating leptin signaling - Qin Tang; Yong Gao; Qinhui Liu; Xuping Yang; Tong Wu; Cuiyuan Huang; Ya Huang; Jinhang Zhang; Zijing Zhang; Rui Li; Shiyun Pu; Guorong Zhang; et al. (Elsevier, 2020)
Objective: Sirt6 is an essential regulator of energy metabolism in multiple peripheral tissues. However, the direct role of Sirt6 in the hypothalamus, specifically pro-opiomelanocortin (POMC) neurons, controlling energy balance has not been established. Here, we aimed to determine the role of Sirt6 in hypothalamic POMC neurons in the regulation of energy balance and the underlying mechanisms. Methods: For overexpression studies, the hypothalamic arcuate nucleus (ARC) of diet-induced obese mice was targeted bilaterally and adenovirus was delivered by using stereotaxic apparatus. For knockout studies, the POMC neuron-specific Sirt6 knockout mice (PKO mice) were generated. Mice were fed with chow diet or high-fat diet, and body weight and food intake were monitored. Whole-body energy expenditure was determined by metabolic cages. Parameters of body composition and glucose/lipid metabolism were evaluated. Results: Sirt6 overexpression in the ARC ameliorated diet-induced obesity. Conversely, selective Sirt6 ablation in POMC neurons predisposed mice to obesity and metabolic disturbances. PKO mice showed an increased fat mass and food intake, while the energy expenditure was decreased. Mechanistically, Sirt6 could modulate leptin signaling in hypothalamic POMC neurons, with Sirt6 deficiency impairing leptin-induced phosphorylation of signal transducer and activator of transcription 3. The effects of leptin on reducing food intake and body weight and leptin-stimulated lipolysis were also impaired. Moreover, Sirt6 inhibition diminished the leptin-induced depolarization of POMC neurons. Conclusions: Our results reveal a key role of Sirt6 in POMC neurons against energy imbalance, suggesting that Sirt6 is an important molecular regulator for POMC neurons to promote negative energy balance.